A Novel In vitro Model for Studying the Interactions Between Human Whole Blood and Endothelium - Nordling, Sofia (J Vis Exp, 2014)
The majority of all known diseases are accompanied by disorders of the cardiovascular system. Studies into the complexity of the interacting pathways activated during cardiovascular pathologies are, however, limited by the lack of robust and physiologically relevant methods. In order to model pathological vascular events we have developed an in vitro assay for studying the interaction between endothelium and whole blood. The assay consists of primary human endothelial cells, which are placed in contact with human whole blood. The method utilizes native blood with no or very little anticoagulant, enabling study of delicate interactions between molecular and cellular components present in a blood vessel. We investigated functionality of the assay by comparing activation of coagulation by different blood volumes incubated with or without human umbilical vein endothelial cells (HUVEC). Whereas a larger blood volume contributed to an increase in the formation of thrombin antithrombin (TAT) complexes, presence of HUVEC resulted in reduced activation of coagulation. Furthermore, we applied image analysis of leukocyte attachment to HUVEC stimulated with tumor necrosis factor (TNFα) and found the presence of CD16(+) cells to be significantly higher on TNFα stimulated cells as compared to unstimulated cells after blood contact. In conclusion, the assay may be applied to study vascular pathologies, where interactions between the endothelium and the blood compartment are perturbed.